2020
DOI: 10.3390/ani11010001
|View full text |Cite
|
Sign up to set email alerts
|

Multienzyme Super-Dosing in Broiler Chicken Diets: The Implications for Gut Morphology, Microbial Profile, Nutrient Digestibility, and Bone Mineralization

Abstract: Optimizing gut health has a large impact on nutrient digestibility and bioavailability, and super-dosing feed enzymes may be one solution to achieve this. A 42-day grow-out trial was conducted using 192 Ross 308 broilers to determine if super-dosing Natuzyme at 0 g/t, 350 g/t, 700 g/t, and 1000 g/t dose rates could improve the gut morphology, alter the cecal microbial profile, enhance bone mineralization, and improve nutrient digestibility of a wheat–corn–soybean diet (six replicates per treatment, eight birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…Gibson et al found that via promoting lactic acid bacteria development in the hindgut, the hydrolysis products of enzymes may subtly inhibit the growth of some pathogens 73 . However, the current findings contradict those of Madigan-Stretton et al and Lourenco et al who revealed no significant prevalence for any connected bacterial species and no variations in microbial diversity across all multienzyme natuzyme treatment groups 48,74 .…”
Section: Indirect Effect Of Anti-toxin Multienzymes On Immunitycontrasting
confidence: 99%
See 2 more Smart Citations
“…Gibson et al found that via promoting lactic acid bacteria development in the hindgut, the hydrolysis products of enzymes may subtly inhibit the growth of some pathogens 73 . However, the current findings contradict those of Madigan-Stretton et al and Lourenco et al who revealed no significant prevalence for any connected bacterial species and no variations in microbial diversity across all multienzyme natuzyme treatment groups 48,74 .…”
Section: Indirect Effect Of Anti-toxin Multienzymes On Immunitycontrasting
confidence: 99%
“…Farmers must improve and maintain optimum digestive health in their birds since it leads to an enhanced performance index, enhanced feed utilization, and improved weight gain 47 . By breaking down macromolecules, modifying broiler gut physiology, and modifying the bacterial composition, multienzyme would enhance digestive health and increase the digestibility of nutrients in broilers 48 . This boost in growth performance may be triggered by the impacts of the reduction in the clostridia count and its secreted endotoxin, as well as the removal of the mycotoxins and their bad effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, conventional broilers in the current study were found to have a single amplicon sequence variant of Oscillibacter , Lachnospiracea NK4A136, and Ruminococcus gauvreauii that were differentially abundant in the ileum on day 7. Both Oscillibacter and Lachnospiracea NK4A136 are short chain fatty acid producers while Ruminococcus gauvreauii may be involved with feed efficiency ( Madigan-Stretton et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poultry produce a variety of digestive enzymes. However, due to the presence of anti-nutritive factors that endogenous enzymes cannot combat, endogenous enzyme digestion alone leaves up to 25% of feed undigested (Celi et al, 2017;Madigan-Stretton et al, 2021). As a result, the significance of gut health in animal production highlights the need to improve food processing and nutrient utilization, as well as product performance and vitality (Burden, 2020).…”
Section: Introductionmentioning
confidence: 99%